Pengaruh Pemberian Daun Pepaya (Carica Papaya L) terhadap Income Over Feed Cost (IOFC) dan Pertambahan Berat Badan pada Ayam Buras (Gallus Gallus domesticus): The Effect of Giving Papaya Leaves (Carica Papaya L) on Income Over Feed Cost and Wight Gain in Free-Range Chicken (Gallus Gallus domesticus) - Wahyuddin; Suci Ananda; Amriana Hifizah; Muhammad Arsan Jamili; Khaerani Kiramang (Universitas Islam Negeri Alauddin Makassar, 2023)
In raising free-range chickens, there are obstacles that must be considered in maintenance, namely the length of time of maintenance related to the cost of feed, so other alternatives are needed that can be used to overcome this problem, one of which is by using papaya leaves. This study determined the effect of giving papaya leaves (Carica papaya L) on Income Over Feed Costs and average daily gain on Kampung KUB chicken (Gallus gallus domesticus). This study used a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatment consisted of P0 (Control Treatment); P1=Commercial feed + 2% papaya leaf powder); P2=Commercial feed+4% papaya leaf powder); P3 = Commercial feed + 6% papaya leaf powder) P4 = Commercial feed + 8% papaya leaf powder). The variables observed in this study are Income Over Feed Cost and average daily gain. The data obtained is analyzed using analysis of variance from RAL and followed by Duncan's test if the results are significant. The results showed that by giving papaya leaf powder (Carica papaya L) in free-range chicken rations the results did not have a significant effect (P>0.05) on Income Over Feed Cost (IOFC) with the treatment P0 19,307, P1 20,070, P2 18,808, P3 18,798, P4 18,506 and average daily gain (PBB), for giving flour the best papaya leaf is given at a concentration of 2% compared to a concentration of 8% papaya leaf flour with the treatment P0 172,45, P1 174,46, P2 169,44, P3 173,89, P4 171,52. The conclusion of the study was that giving papaya leaf powder (Carica Papaya L) in KUB chicken rations did not have a significant effect (P>0.05) on Income Over Feed Cost (IOFC) and Weight Gain, however, it did have a good effect on Income Over Feed Cost (IOFC) and Weight Gain can be seen from the average results because these alternative feeds can make feed costs efficient during maintenance.